2014
DOI: 10.1021/es504375t
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nanoparticle-Induced Activation of Plasma Membrane H+-ATPase Promotes Stomatal Opening in Arabidopsis thaliana

Abstract: Engineered nanomaterials (ENMs) enable the control and exploration of intermolecular interactions inside microscopic systems, but the potential environmental impacts of their inevitable release remain largely unknown. Plants exposed to ENMs display effects, such as increase in biomass and chlorophyll, distinct from those induced by exposure to their bulk counterparts, but few studies have addressed the mechanisms underlying such physiological results. The current investigation found that exposure of Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 55 publications
(122 reference statements)
2
57
0
Order By: Relevance
“…Other authors evidenced the potential translocation of fullerenes (Lin et al, 2009), CeO 2 (Hong et al, 2014) and nZVI in macrophytes. Kim et al (2014Kim et al ( , 2015 suggested that when A. thaliana seeds are treated with nZVI the induced OH radicals may thin or open plant seed coat and, thus, Li et al (2015) suspected that nZVI could penetrate A. hypogaea seed coat increasing water uptake promoting seedling development.…”
Section: Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors evidenced the potential translocation of fullerenes (Lin et al, 2009), CeO 2 (Hong et al, 2014) and nZVI in macrophytes. Kim et al (2014Kim et al ( , 2015 suggested that when A. thaliana seeds are treated with nZVI the induced OH radicals may thin or open plant seed coat and, thus, Li et al (2015) suspected that nZVI could penetrate A. hypogaea seed coat increasing water uptake promoting seedling development.…”
Section: Microscopymentioning
confidence: 99%
“…Lee et al (2010) showed that Fe 3 O 4 ENPs in Arabidopsis thaliana did not significantly affect seed germination and the number of produced leaves, while the root elongation was negatively influenced at all exposure concentrations (400, 2000, and 4000 mg Fe 3 O 4 /L). Kim et al (2014Kim et al ( , 2015 investigated the effect of nZVI on A. thaliana root elongation showing an enhanced growth by 150-200% at 0.5 g/L compared to the blank. Further studies on A. thaliana evidenced that nZVI triggered high plasma membrane H þ -ATPase activity resulting in a 5-fold higher stomatal opening than in unexposed plants (Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that SiO 2 NPs were transported from roots to shoot via xylem sap in rice and CeO 2 NPs also can be absorbed by this way (Le et al 2014(Le et al , 2015. Since xylem sap of rice contains Fe elements, we (Kim et al 2014), the nanoparticles of transport mechanism.…”
Section: Tem Imagingmentioning
confidence: 99%
“…For example, low conductivity of the plasma membrane to H + improves the buffering capacity in the cell, as well as improving the capacity of cells to transfer H + to the extracellular environment to reduce proton concentrations inside the cells . Moreover, cells can produce some enzymes such as H + ‐ATPase and extracellular acid phosphatase enzymes which could enhance the tolerance to acidic conditions in some algae …”
Section: Incidence Of Algae In Response To Climate Changementioning
confidence: 99%